Coregonus laurettae Bean 1881 ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Coregonus laurettae Bean, 1881. Bering Cisco. To 48 cm (18.9 in) FL (Alt 1973). Chukchi Peninsula, eastern Siberia to Alaska; Oliktok Point, Beaufort Sea, Alaska to Kenai Peninsula, northern Gulf of Alaska. Primarily freshwater and coastal marine habitats, some populations anadromous. All except maximum length in Mecklenburg et al. (2002). ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 52, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...